Efektivitas Cybermedia Sebagai Sarana Komunikasi Dakwah Modern - Nazarullah Nazarullah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2017)
This article discusses the effectiveness of cybermedia as a means of modern da'wah communication, focusing on several issues, namely the general description of cybermedia, the meaning of dakwah and the possibility of internet becoming the medium of da'wah and strategy and utilization of internet in da'wah in modern era. Through this article the authors argue that in this era of information technology, it should be Muslims in general and the preachers in particular take advantage of new media the Internet as a means of preaching to be more effective. Furthermore, by making cybermedia or internet as a medium of da'wah today, the real actors of da'wah have confirmed the pattern of modern dakwah.